The long-term scientific benefits of a space economy. (August 2016) - Crawford, Ian A.
Abstract: Utilisation of the material and energy resources of the Solar System will be essential for the development of a sustainable space economy and associated infrastructure. Science will be a major beneficiary of a space economy, even if its major elements (e.g. space tourism, resource extraction activities on the Moon or asteroids, and large-scale in-space construction capabilities) are not developed with science primarily in mind. Examples of scientific activities that would be facilitated by the development of space infrastructure include the construction of large space telescopes, ambitious space missions (including human missions) to the outer Solar System, and the establishment of scientific research stations on the Moon and Mars (and perhaps elsewhere). In the more distant future, an important scientific application of a well-developed space infrastructure may be the construction of interstellar space probes for the exploration of planets around nearby stars.